Valorization of agro-industrial wastes towards the production of rhamnolipids. (July 2016) - Gudiña, Eduardo J.; Rodrigues, Ana I.; de Freitas, Victor; Azevedo, Zélia; Teixeira, José A.; Rodrigues, Lígia R.
Highlights: Oil mill wastewater (OMW) was evaluated as an inductor of rhamnolipid production. A culture medium containing corn steep liquor, molasses and OMW was designed. Pseudomonas aeruginosa #112 produced 5.1 g rhamnolipid/l using that medium. The critical micelle concentration of the purified rhamnolipids was 13 mg/l. This medium represents a sustainable alternative for rhamnolipid production. Abstract: In this work, oil mill wastewater (OMW), a residue generated during olive oil extraction, was evaluated as an inducer of rhamnolipid production. Using a medium containing as sole ingredients corn steep liquor (10%, v/v), sugarcane molasses (10%, w/v) and OMW (25%, v/v), Pseudomonas aeruginosa #112 produced 4.5 and 5.1 g of rhamnolipid per liter in flasks and reactor, respectively, with critical micelle concentrations as low as 13 mg/l. Furthermore, in the medium supplemented with OMW, a higher proportion of more hydrophobic rhamnolipid congeners was observed comparing with the same medium without OMW. OMW is a hazardous waste which disposal represents a serious environmental problem; therefore, its valorization as a substrate for the production of added-value compounds such as rhamnolipids is of great interest. This is the first report of rhamnolipid production using a mixture of these three agro-industrial by-products, which can be useful for the sustainable production of rhamnolipids.